PERUBAHAN KEGIATAN EKONOMI MASYARAKAT ADAT BADUY LUAR - Melawati Muhtaromah; Nur Holisah; Ujang Jamaludin; Ila Rosmilawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The results of the pre-research also show that the family has a major role in the economic education process of the Baduy community. Parents teach children with habituation, example, and direct mentoring methods. There is no coercion or punishment in the learning process, but it is done through the process of observation (modeling) and imitation (imitation), which is the traditional method in indigenous peoples' education. In addition to the family, the community environment also plays a role in supervising, guiding, and ensuring that children continue to follow customary rules while engaging in economic activities. In the context of Baduy culture, the learning process is not only a function of formal schooling, but a function of the collective environment. This is in line with Vygotsky's thinking about the zone of proximal development which emphasizes that learning occurs through social interaction with more skilled people. Children learn through direct involvement with adults, not through abstract theory. They learn the value of life, not just economic competence